Combinations of Immunotherapy and Radiation in Cancer Therapy - Vatner, Ralph E.; Cooper, Benjamin T.; Vanpouille-Box, Claire; Demaria, Sandra; Formenti, Silvia C. (Frontiers in Oncology, 2014)
The immune system has the ability to recognize and specifically reject tumors, and tumors only become clinically apparent once they have evaded immune destruction by creating an immunosuppressive tumor microenvironment. Radiotherapy can cause immunogenic tumor cell death resulting in cross-priming of tumor specific T-cells, acting as an in situ tumor vaccine; however, radiotherapy alone rarely induces effective anti-tumor immunity resulting in systemic tumor rejection. Immunotherapy can complement radiotherapy to help overcome tumor induced immune suppression, as demonstrated in pre-clinical tumor models. Here we provide the rationale for combinations of different immunotherapies and radiotherapy, and review the pre-clinical and emerging clinical evidence for these combinations in the treatment of cancer.